Could Nintendo’s Animal Crossing be a tool for conservation messaging? - Jessica C. Fisher (Wiley, 2021)
Abstract The current extinction crisis demands worldwide commitment to conservation across all sectors of society. By transcending the traditional disciplinary boundaries, conservationists can reach new audiences to communicate pro‐conservation knowledge, education and awareness messages. There are approximately 2.7 billion video‐gamers worldwide, with millions more joining as a result of global lockdowns. In March 2020, Animal Crossing: New Horizons was released by Nintendo, fast becoming the second‐best selling video game ever in Japan, and selling over 26.4 million units worldwide. Unlike many popular video games, its unique premise involves players creating an island, growing vegetation, catching wildlife and donating fossils and species to a museum. The game has been praised for its positivity, escapism and measurable benefits to mental well‐being. Here, we articulate how different features of the game, including the islands, their biodiversity and inhabitants, encourage players to exhibit pro‐conservation behaviours and attitudes (e.g. recycling litter, or planting a diversity of flowers), as well as improving players’ knowledge about the diversity of relatively little known taxa (marine and freshwater fishes and invertebrates). We also highlight where pitfalls exist (e.g. encouraging the collection of threatened species). We principally frame these discussions in the context of Japan's cultural relationship with the natural world, including its history of insect‐collecting and its management of green spaces. We conclude by outlining some recommendations about potential improvements to future releases, or for similar games, that could further promote conservation messaging. This perspective sheds light on the avenues through which Animal Crossing: New Horizons encourages pro‐conservation knowledge, attitudes and behaviours of its international audience, with potential for these experiences to translate into real‐world conservation actions. During a critical time in humanity's history, video gaming could therefore provide a huge opportunity for communicating conservation messages to billions of people worldwide. A free Plain Language Summary can be found within the Supporting Information of this article.